Investigating Turn-Taking Patterns on Students’ Conversation on Synchronous Discussion - Sylvia Putri Ainurrifah; Dian Ratnawati; Irma Khoirot Daulay (Universitas Islam Negeri Palopo, 2026)
This study investigates turn-taking patterns and students' management of the conversational floor during synchronous online discussions in an English as a Foreign Language (EFL) setting. As synchronous platforms grow more prevalent in language learning, understanding how students organize interaction in digitally mediated situations becomes increasingly crucial. The data were collected through a single recorded Zoom discussion involving three EFL students, using a descriptive qualitative approach guided by Conversation Analysis (CA). This study investigates how platform affordances and pedagogical expectations influence turn-taking behavior in teacher directed synchronous classroom context. In contrast, previous CA studies in online EFL contexts that generically address interactional competence. The findings demonstrate that turn-taking in synchronous settings is highly regulated and heavily influenced by teacher oversight. Turn initiation was primarily through teacher nomination, while student self-selection emerged only at clear transition points. Significantly, no were no instances of overlap or interruption were observed, demonstrating that participants complied with platform norms and institutional requirements. Students also utilized self-initiated repair strategies, including hesitations, repetitions, and reformulations to maintain the language challenges and maintain speakership. Overall, turn-taking in synchronous EFL discussions was systematic and non-competitive, influenced by technological affordances and pedagogical framework. Furthermore, the findings of the study enhance the theoretical comprehension of how technologically mediated environments shape interactional patterns and turn-taking frameworks in instructed language-learning settings. Despite the small sample of three participants, these findings provide preliminary insights into interactional approaches within online language classes and highlight the necessity for instructional strategies that encourage equitable participation in synchronous learning settings.